Transcatheter closure of patent ductus arterious at Chris Hani Baragwanath hospital and the importance of the shape and size of the patent ductus - Adams, Paul Ernest (My University, 2016)
Objectives Review outcomes of transcatheter closure of patent ductus arteriosus (PDA), role of PDA shape and changes in practice over time. Methods Retrospective analysis of patient files and clinic database performed on children who had transcatheter PDA closure at Chris Hani Baragwanath Hospital between 01/01/1993 and 30/06/2008. Results Over 15 years, 1254 PDAs were diagnosed, of which 293 required closure (167 with surgery and 139 transcatheter). Median age at transcatheter closure was 1.8 years (IQR=1-4.5years); 66.2% were female (92/139). Mean PDA diameter was 3.2mm (sd=1.6mm), with an average 2:1 shunt. Transcatheter closure was performed using COOK® Flipper coils (n= 93; 18 required multiple coils) or Amplatzer™ devices (n=46: 37 with ADO1, 8 AVP and 1 ADO2). Repeat procedures were needed in 20 children: Early occlusion rates for coils were 52% (39/75); late occlusion occurred in 90.6% (68/75). Amplatzer™ devices, available since 2003, are now overwhelmingly used. For ADOs, early occlusion rates were 94.3% (33/35) with 100% late occlusion. Successful closures were associated with PDA shape, with 88% closed with type A and E, 50% type B, 28% type C and 0% type D. Surgical closure reduced over time: from 94 weeks (1993–1997), to 40 weeks (1998–2002) and 32 weeks(2003–2008). Conclusion Transcatheter PDA occlusion is safe and effective in this setting, with outcomes similar to reports elsewhere. Shape and size of PDAs are important determinants of device selection and procedure outcome. Transcatheter occlusion helps minimise surgical waiting lists. Overall findings support more widespread use of this procedure in similar settings.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for the degree in Master of Medicine in Paediatrics Johannesburg 2016